A bibliometric analysis of acupuncture for cerebral infarction from 1993 to 2023 - Zhao, Yanqing; Huang, Li; Li, Wentao; Cai, Li (Frontiers in Neurology, 2024)
Objective This research aims to explore the trends and knowledge domain of acupuncture for cerebral infarction through bibliometrics. Methods Publications related to acupuncture for cerebral infarction were retrieved from the Web of Science core collection database from 1993 to December 31, 2023. A domain knowledge graph was then constructed using VOSviewer, CiteSpace, GraphPad Prism, and Scimago Graphica. Results The cumulative publication trend shows a steady increase over the years, with China being the most productive country. Notably, Europe exhibits significant close collaboration. Institutional cooperation is primarily observed among Chinese universities specializing in traditional Chinese medicine. Tao Jing is the most prolific author, with his highest number of publications is in “Stroke” journal, and Acupuncture Electro Therapeutics Research is the significant journal. Zhang SH is the most cited author, and Si QM is a prominent author in this field. Rehabilitation treatment after cerebral infarction emerges as a prevalent research focus, with nerve regeneration being a keyword. Long EZ's 1989 paper, published in the journal Stroke, holds significant importance. The prominent papers are Donnan et al. and Wu et al., which covers the following topics: “population-based study,” “Baihui Acupoint,” “memory deficits,” “neurotrophic factor,” and “randomized trial.” Conclusion This bibliometric analysis of acupuncture for cerebral infarction offers insights into the Web of Science database, delineates a knowledge map of countries, authors, institutions, cited authors, keywords, cited references in the field of acupuncture for cerebral infarction, which has a momentous guiding significance for quickly and accurately positioning the key information in the field.